2021
DOI: 10.1038/s41598-021-99012-6
|View full text |Cite
|
Sign up to set email alerts
|

A modeling study on utilizing low temperature sprayed In2S3 as the buffer layer of CuBaSn(S, Se) solar cells

Abstract: This study represents the investigation of In2S3 thin films as an electron transport layer in the CuBaSn(S, Se)-CBT(S, Se) solar cells, which have been deposited using the Chemical Spray Pyrolysis method. For studying the electrical properties of films such as conduction and valence band, carrier densities, Fermi level, flat band potential, and semiconductor type, the Mott–Schottky analysis has been used. UV–VIS, XRD, and FESEM have been applied to investigate the optical properties of the layers and the layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 53 publications
(29 reference statements)
2
4
0
Order By: Relevance
“…From Figure 7(c) and 7(d), it was identified that the direct energy band gaps of the films were found as 2.32, 2.52 and 2.56 eV and the indirect energy band gaps of the films were found as 2.08, 2.24 and 2.36 eV, for the samples IS, IS-350 and IS-450, respectively. The observed band gap values were found to be in concordance with the reported band gap values for In2S3 films in previous studies [25,[50][51][52]. Interestingly, it was found that the high temperature treated films had higher Eg than as-deposited films.…”
Section: Optical Characterizationsupporting
confidence: 91%
“…From Figure 7(c) and 7(d), it was identified that the direct energy band gaps of the films were found as 2.32, 2.52 and 2.56 eV and the indirect energy band gaps of the films were found as 2.08, 2.24 and 2.36 eV, for the samples IS, IS-350 and IS-450, respectively. The observed band gap values were found to be in concordance with the reported band gap values for In2S3 films in previous studies [25,[50][51][52]. Interestingly, it was found that the high temperature treated films had higher Eg than as-deposited films.…”
Section: Optical Characterizationsupporting
confidence: 91%
“…With this regard, we explored the properties of ZrS 2 to a great extent for diverse emerging chalcogenide thin-film solar cells such as SnS, Sb 2 Se 3 , Cu 2 SnS 3 , CuSb(S,Se) 2 , and Cu 2 BaSn(S,Se) 4 using SCAPS-1D for the first time. Moreover, the SCAPS-1D simulation studies are consistent with the experimental results, [37,38] witnessing its reliability in understanding the solar cells' function. Therefore, we extensively studied the effect of bandgap, thickness, carrier concentration, and defect density of ZrS 2 on the performance of diverse emerging chalcogenide thin-film solar cells by unveiling its unique properties that have not been explored.…”
Section: Introductionsupporting
confidence: 69%
“…The peaks of In 2 S 3 are well matched with the JCPDS card no. 00-25-0390, which confirms the crystallization of pure tetragonal phase In 2 S 3 . After the surface functionalization of S-C 3 N 4 -dots on the surface of In 2 S 3 nanosheets, the XRD peaks remain intact and no other significant peak is observed due to the S-C 3 N 4 -dots.…”
Section: Resultsmentioning
confidence: 64%